Grundtvigs nordisk-mytologiske billedsprog - et mislykket eksperiment? - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 1994)
Grundtvig ’s Norse Mythological Imagery - An Experiment that Failed?By Flemming Lundgreen-Nielsen Since his early youth, Grundtvig worked frequently and diligently with Norse mythology. From 1805 to 1810 he tried in a scholarly way to sort out its original sources and accordingly its ancient meanings, though Grundtvig even as a philologist preferred to give spontaneous enthusiasm aroused by a synthetic vision a priority above linguistic proofs (Norse Mythology, 1808). After a pause of some years, Grundtvig in 1815 returned to Norse mythology, allowing himself a more free and subjective interpretation in lieu of an all-encompassing conception. From now on aiming to turn the Norse myths into an accessible store of modeme national imagery, he adapted a favourable evaluation of Snorri’s Edda, which until then he had been regarding as late, distorted information.Drawing mainly upon previously unprinted material the paper demonstrates, how Grundtvig around 1820, 1832, in the 1840’s and during the Schleswig-Holstein war 1848-50 tried to revive Snorri’s Edda for actual commonday use. To put Grundtvig’s opinions in a historical perspective, other contemporary statements are included, such as a Copenhagen press and pamphlet feud on the potential usefulness of Norse mythology to sculptors and painters (1820-21) and a public lecture in favour of Greek mythology and Christian civilization given by professor Madvig (1844).Grundtvig’s own attempts to mobilize the Norse gods in current affairs are illustrated in selected examples from his poetical works. The conclusion indicates that his project was a failure: none of his ballads and poems popular then and today deal with Norse mythology, and although his Norse Mythology, 1832, became a handbook for teachers of the Folk Highschools, neither later poets nor philosophers employed the Norse mythological imagery he recommended. In the war 1848-50 Grundtvig wanted to take advantage of situations from myths and legends such as Thor battling the giant Hrungnir and prince Uffe the Meek killing two Saxons, but the majority of the Danes cherished heroes of the people such as the brave unknown army soldier celebrated in a 1858-statue and the little homblower from a bestselling verse epic. At the end of his life, Grundtvig continued to write poetry in Norse mythological terms, but apparently made no efforts to get his manuscripts printed - why is not known.Among the reasons to be suggested for the failure of Grundtvig’s Norse mythological imagery, the victorious ideas in Romantic 19. century poetry and arts pertaining to originality and individualism, the prominent place of traditional classical mythology in the minds of the cultured public, and the political emphasis in the mid century period on democratization are probably most decisive.Finally attention is given to the fact that the proverbial phrase about ’freedom to Loki as well as to Thor’, the only surviving popular dictum from Grundtvig’s Norse mythological writings, almost invariably is misunderstood to be a token of boundless tolerance to both parties in the struggle between good and evil. However, several instances can be mentioned to prove that Loki, mythologically half god, half giant, in Grundtvig’s understanding does not represent evil as much as a gifted intellectualism without religious faith, possessing potential to acquire it.An English version of the paper with less regard to quotes from unprinted Grundtvig manuscripts and more attention to introductory paragraphs on Danish literary history is published in Andrew Wawn (ed.): Northern Antiquity. The Post-Medieval Reception of Edda and Saga, Hisarlik Press, 1994, p. 41-67.